Dampak Integrasi Ekonomi ASEAN terhadap Permintaan Industri Manufaktur Indonesia - Imam Mukhlis (Jurnal Ekonomi dan Studi Pembangunan, 2009)
This research seeks to answer the question: "Whether the trade creation emerges in demand of Indonesian manufacture industry import during the years of 1980-2005 as the impact of ASEAN economic integration?" By using time series analysis of variables import values of manufacture industry, GDB, and volatility of exchange rates, the result shows that there is no trade creation toward the demand of manufacture industry import. This is due to no significant influence of GDB on the demand of manufacture industry import.Keywords: economic integration, manufacture industry, trade creation